(untitled) (Research, Society and Development, 2022)
This article aims to make reflections about the initial training of teachers of the Pedagogy Courses from the implementation of the Common National Base for the Initial Training of Teachers of Basic Education- Resolution CNE/CP nº 2/2019, building a parameterization with the CNE/CP Resolution N° 1/2006, is the latest fruit of historical struggles in the educational area. The construction of the research problem revolves around the professional constitution and the disciplinary/epistemological knowledge needed by the Pedagogues to teach the discipline "Teaching Geography". In this sense, we analyzed the disciplines programs of three public institutions of the Geography Teaching component. To debate about the foundation on Geography Teaching we align ourselves with Pontuschka, Paganelli, Cacete (2009). Our considerations show that the implications, in a specific way/ in the Component Teaching of Geography, and in general/ in the pedagogical formation of (o) Pedagogy(a), brought by BNC-Training 2019, is based on a productivist conception of education that continues the neoliberal ideology, based on the epistemology of practice which empties the contributions of socially constituted knowledge. In addition, of course, to strengthening the ideas of the dualistic school, the reduction of the role of the teacher to execute scripts prepared by third parties and the blaming of teachers for the poor results of standard educational indices based on large-scale evaluations/tests.